The effectiveness of additional screening examinations for children and adolescents in Germany: a longitudinal retrospective cohort study - Kathrin Krüger; Anne-Marie Lapstich; Katrin Christiane Reber; Stephanie Sehlen; Sebastian Liersch; Christian Krauth (BMC, 2023)
Abstract Background Continuous medical care is particularly important in childhood and adolescence. Since there are gaps in regular care in Germany, various health insurance providers offer to cover additional examinations (e.g., U10, U11, J2) to ensure ongoing paediatrician visits. However, the question arises as to whether these examinations are effective. Thus, the main objective of this study is to determine whether participation in the U10, U11 or J2 examinations leads to more frequent and earlier diagnosis and treatment of age-specific diseases. Methods The analyses are based on administrative claims data from a statutory health insurance fund. For each examination, an intervention group (IG) is formed and matched with a corresponding control group (CG). Descriptive analyses include proportion with diagnosis and treatment, average age of diagnosis and treatment initiation. Hypothesis testing is performed using methods appropriate to each. In addition, subgroup analyses and binominal logistic regression models are conducted. Results More diagnoses are detected in IG, irrespective of subgroups. Additionally, diagnoses are made slightly earlier on average in IG. In the total samples, more therapies are initiated in IG, and slightly earlier. Considering only diagnosed cases, more therapies are initiated in CG but continue to be started earlier in IG. Regression models show that participation in the examinations has the highest predictive power for detecting a diagnosis. The presence of a chronic disease and sex - male at the U10 and U11 and female at the J2 - are also significantly associated. The models further show that nationality, unemployment of parents and region also have a significant influence in some cases, whereas school-leaving qualification, vocational qualification and income of parents do not. Considering the initiation of treatment in overall samples, the models show similar results, but here the presence of a chronic illness has the highest predictive power. Conclusion The results indicate that participation in the examinations leads to significantly more diagnoses and, in the overall samples, significantly more treatments. In addition, diagnoses were made somewhat earlier and therapies were initiated somewhat earlier. In the future, it would be useful to investigate the U10, U11 and J2 examinations over a longer time horizon to determine whether the statistically significant difference found is also clinically relevant, i.e., earlier diagnosis and initiation of therapy lead to prevention of manifestation or progression of the diagnosed diseases and to avoidance of secondary diseases. Trial registration German Clinical Trials Register (DRKS), DRKS-ID: DRKS00015280. Prospectively registered on 18 March 2019.